Law, governance, and social-psychological pathways to bridging environmental protection and resource exploitation conflicts - Sami Najm Abed Al-Nuaimi; Imad Obaid Jasim; Khaled Obeid Jazi; Zahraa Mahdi Dahsh; Hasan Ali Abbas (Environment and Social Psychology, 2025)
The conflict that the policy makers have been continuously facing is in between protecting the environment and exploiting the natural resources economically. The paper assesses the effectiveness of legal tools in reducing environmental degradation by facilitating controlled utilization of resources, and suggests a mixed method, based on analysis of environmental impacts, measurement of institutional resiliency, mobilization of stakeholders, and analysis of comparative law. Using new statistical method and cross-regional analysis, the paper reveals that legal transparency, enforceability and participative government play significant roles in driving up the levels of compliance and sustainability. Among the most useful works, one can distinguish introducing the mediators of a psychological and cultural analysis into the analysis explicitly. Findings indicate that perceptions of justice, institutional trust and cohesion are relevant in predicting the extent to which legal systems influence the propensity to comply. Not only did the areas that were characterized by a strong institutional base and a high level of stakeholder engagement contribute to the reduction in ecological degradation, but were also more legitimate and had a greater permanence of policy over time. Cultural dimensions define once again that there should be the accommodation of the models of governance to the local values so that these models do not contribute to resistance and aggravation of the terms of conflict. The results show that the law design is not just a design that has no social legitimacy whatever. The organization of outcomes in good governance, in combination with equal portions of distributive justice, mixed participation and responsive institutional capacity. Such participatory and culture-specific aspects of law also enable more ecological results in relation to dynamically changing environmental and socio-political pressures and are found in the application of scenario-based modelling. The present study gives a transferable and sensitive description of how to come up with approaches based on the law, which are politically competent, in order to make environmental management sensitive to environmental sustainability and social justice.